Hubungan Seksual Suami-Istri dalam Perspektif Gender dan Hukum Islam - Umi Khusnul Khatimah (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: Marital Sexual Relations within the Perspective of Gender and Islamic Law. This article explains that the rights of sexual relations of men and women within the institutional framework of marriage are the same. The assumption of jurisprudence which is source from several hadith has been adopted as a male hegemony without considering the substance and context of the Hadith. Meanwhile, the Quran describe the balancing of rights of men and women within sexual relationships. This study offers an approach to the study in the case of sexual relations of men and women to look at usûl al-fiqh as a critical foundation in law making. In social and cultural analysis, it can be seen that the construction law is heavily influenced by longstanding habits. Therefore, universal values   should be seen as a response to the formation of the current law.Keywords: sexual relation, Islamic law, genderAbstrak: Hubungan Seksual Suami-Istri dalam Perspektif Gender dan Hukum Islam. Artikel ini menjelaskan bahwa hak-hak hubungan seksual laki-laki dan perempuan dalam kerangka institusi pernikahan adalah setara. Asumsi fikih yang bersumber dari beberapa Hadis diadopsi sebagai hegemoni laki-laki tanpa menimbang substansi dan konteks Hadisnya. Sementara Alquran menjelaskan keseimbangan hak laki-laki dan perempuan dalam hubungan seksual. Studi ini menawarkan suatu pendekatan pada kajian hukum Islam dengan kasus hubungan seksual laki-laki dan perempuan untuk melihat ushul fikih sebagai pondasi kritis dalam pengambilan hukum. Dalam analisis sosial dan budaya terlihat bahwa konstruksi hukum banyak dipengaruhi oleh kebiasaan yang sudah berlangsung lama. Untuk itu, nilai-nilai universal perlu dilihat sebagai jawaban dalam formasi hukum saat ini.Kata Kunci: hubungan seksual, hukum Islam, genderDOI: 10.15408/ajis.v13i2.936